The Role of Tutorials for ESL Students——New Zealand Perspectives - Wang, Shiyun (Advances in Social Sciences Research Journal, 2015)
It is generally known that lectures, as an important teaching form, are widely used in universities all over the world. However, after doing a review of research, Brown (1989, p.458) concluded that this teaching method should also be augmented by other forms of teaching” (cited in Sweeney, O’Donoghue & Whitehead, 2003, p.313,). Thus it is quite necessary to review some other kinds of teaching forms in universities. Tutorial works, which are adopted as a commonplace in New Zealand universities, are very useful elements in helping students better understand lectures and this kind of teaching method exerts a significant role for study in universities of New Zealand. It is just like some people say “Tutoring is an important component in undergraduate education (Encyclopedia of Education, 2003, p.313, cited in Sweeney, O’Donoghue & Whitehead). Since there are various kinds of activities that are often adopted in tutorial works in New Zealand universities, it is necessary to analyze these activities to see the characteristics and the requirements that are needed in tutorial works. This report will review the feature of some main activities that are often used in tutorial works and investigate the skills that are required in such activities from different perspectives. The difficulties for ESL (English as a second language) students in tutorials are also put forward with an investigation about the reason of this problem. Furthermore, some recommendations from my personal point of view will be put forward in order to help those students who want to do graduate study in New Zealand.